2020
DOI: 10.1155/2020/9747826
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a Novel Upregulated lncRNA, A2M-AS1, That Promotes Invasion and Migration and Signifies Poor Prognosis in Breast Cancer

Abstract: Understanding of prognostic factors and therapeutic targets for breast cancer is imperative for guidance of patient care. We studied 1203 tumour samples from the Gene Expression Omnibus (GEO) to evaluate potential genes related to breast cancer. R software was used to analyse differentially expressed long noncoding RNAs (lncRNAs) in the RNA microarray expression profiles GSE45827 and GSE65216 and to identify a series of differentially expressed lncRNAs associated with human breast cancer. Of these lncRNAs, A2M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Three lncRNAs ( A2M-AS1 , C2orf27A , and ZNF667-AS1 ) were identified to be related to the hub FRGs. Among them, A2M-AS1 was reported to be involved in the invasion, migration, and progression of breast cancer ( Fang et al, 2020 ; Liu et al, 2020b ). In addition, A2M-AS1 was also reported to lessen cardiomyocyte injury caused by hypoxia/reoxygenation (H/R) by regulating IL1R2 ( Song et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three lncRNAs ( A2M-AS1 , C2orf27A , and ZNF667-AS1 ) were identified to be related to the hub FRGs. Among them, A2M-AS1 was reported to be involved in the invasion, migration, and progression of breast cancer ( Fang et al, 2020 ; Liu et al, 2020b ). In addition, A2M-AS1 was also reported to lessen cardiomyocyte injury caused by hypoxia/reoxygenation (H/R) by regulating IL1R2 ( Song et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…45 Upregulated A2M‐AS1 was associated with invasion and migration in breast cancer. 46 Besides, LINC00702 enhanced the progression of ovarian cancer through increased EZH2 expression. 47 Then, LINC00702/has‐miR‐4652‐3p/ZEBI axis can promote the progression of malignant meningioma through activating the Wnt/β‐catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA A2M-AS1 is demonstrated to influence the progression of pancreatic cancer. 6 Interestingly, Fang et al have elucidated that lncRNA A2M-AS1 was also enriched in BC, which facilitated BC cell proliferation, invasion, and migration, 7 while the roles of lncRNA A2M-AS1 in BC remain to be further explored. Following the evaluation of the functional relevance of lncRNA A2M-AS1 to BC cell function, this study demonstrated that lncRNA A2M-AS1 regulated BC cell biological activity by sponging miR-146b.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Furthermore, A2M-AS1 elevation has been suggested to be related to poor recurrence-free and metastasis-free survival of BC patients, implying its possible prognostic and therapeutic role in BC. 7 However, whether A2M-AS1 indeed modulates the progression of BC and how the mechanism works remain unsettled. LncRNAs act as competing endogenous RNAs (ceRNAs) by competitively interacting with shared microRNAs (miRNAs).…”
Section: Introductionmentioning
confidence: 99%